2020
DOI: 10.1542/peds.2019-1411
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Experiences of Young Transgender Persons During and After Gender-Affirmative Treatment

Abstract: OBJECTIVES: Early gender-affirmative treatment (GAT) of adolescents may consist of puberty suppression, use of affirming hormones, and gender-affirmative surgeries. This treatment can potentially influence sexual development. In the current study, we describe sexual and romantic development during and after treatment. METHODS: The participants were 113 transgender adolescents treated with puberty suppression, affirmative hormones, and affirmative surgery who were assessed as young adults (38 transwomen and 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
(71 reference statements)
2
10
0
1
Order By: Relevance
“…This is in line with the findings of Veale et al (19) but differed from those of Bungener et al (18) and , who found that transgender identifying adolescents had fewer sexual experiences, and of Korchmaros et al (10), who reported that transgender adolescents had more sexual experiences than their cisgender counterparts. However, earlier research has focused on adolescents referred to mental health services due to symptoms of gender dysphoria (17,18), activist cohorts (19) or they have not focused specifically on transgender identifying youth but rather on LGBTQ youth as whole (10), for example. Our novel contribution is that we compared sexual development between transgender and cisgender youth in a general population sample.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with the findings of Veale et al (19) but differed from those of Bungener et al (18) and , who found that transgender identifying adolescents had fewer sexual experiences, and of Korchmaros et al (10), who reported that transgender adolescents had more sexual experiences than their cisgender counterparts. However, earlier research has focused on adolescents referred to mental health services due to symptoms of gender dysphoria (17,18), activist cohorts (19) or they have not focused specifically on transgender identifying youth but rather on LGBTQ youth as whole (10), for example. Our novel contribution is that we compared sexual development between transgender and cisgender youth in a general population sample.…”
Section: Discussionsupporting
confidence: 87%
“…However, this study focused on LGBTQ adolescents rather than specifically on transgender adolescents. Contrary to this, studies in the Netherlands and in Finland found that adolescents referred to evaluation due to gender dysphoric characteristics had fewer sexual experiences than their peers in the general population (17,18) whereas a Canadian study based on activist material found no difference in the numbers of sexual experiences (19).…”
Section: Introductionmentioning
confidence: 67%
“…Evidence supports the existence of surgical implications for transgender girls who proceed with pubertal suppression (van de Grift et al., 2020 ). Longitudinal data exists to demonstrate improvement in romantic and sexual satisfaction for adolescents receiving puberty suppression, hormone treatment and surgery (Bungener et al., 2020 ). A study on surgical outcomes of laparoscopic intestinal vaginoplasty (performed because of limited genital tissue after the use of puberty blockers) in transgender women revealed that the majority experienced orgasm after surgery (84%), although a specific correlation between sexual pleasure outcomes and the timing of pubertal suppression initiation was not discussed in the study (Bouman, van der Sluis et al., 2016 ), nor does the study apply to those who would prefer a different surgical procedure.…”
Section: Chapter 6 Adolescentsmentioning
confidence: 99%
“…Coleman et al ( 2022 ) claimed that “longitudinal data exists to demonstrate improvement in romantic and sexual satisfaction for adolescents receiving puberty suppression, hormone treatment and surgery.” However, the supporting citation requires scrutiny. Bungener et al ( 2020 ) was a cross-sectional study of 113 young adults, 66% of whom were transmen (most who had undergone mastectomy and gonadectomy, not genital surgery). For its claims of post-surgery increases in sexual experience, it relied on recall of pre-surgical experiences.…”
Section: Risks Of Gender-affirming Medical and Surgical Treatmentsmentioning
confidence: 99%